Aiming for the top: non-cell autonomous control of shoot stem cells in Arabidopsis - Fuchs, Michael; Lohmann, Jan U. (Journal of plant research, 2020)
In multicellular organisms, not all cells are created equal. Instead, organismal complexity is achieved by specialisation and division of labour between distinct cell types. Therefore, the organism depends on the presence, correct proportion and function of all cell types. It follows that early development is geared towards setting up the basic body plan and to specify cell lineages. Since plants employ a post-embryonic mode of development, the continuous growth and addition of new organs require a source of new cells, as well as a strict regulation of cellular composition throughout the entire life-cycle. To meet these demands, evolution has brought about complex regulatory systems to maintain and control continuously active stem cell systems. Here, we review recent work on the mechanisms of non cell-autonomous control of shoot stem cells in the model plant Arabidopsis thaliana with a strong focus on the cell-to-cell mobility and function of the WUSCHEL homeodomain transcription factor.
Gesehen am 04.06.2020